Quality of warfarin therapy and risk of stroke, bleeding, and mortality among patients with atrial fibrillation: results from the nationwide FinWAF Registry. Issue 6 (19th March 2017) - Lehto, Mika; Niiranen, Jussi; Korhonen, Pasi; Mehtälä, Juha; Khanfir, Houssem; Hoti, Fabian; Lassila, Riitta; Raatikainen, Pekka
Abstract: Purpose: The most important management strategy in atrial fibrillation (AF) patients is preventing stroke with oral anticoagulants. Warfarin is still used as a first‐line anticoagulant, although non‐vitamin K antagonist oral anticoagulants are currently recommended to manage AF. Using a large, unselected national sample of AF patients, we evaluated the relationships between quality of warfarin therapy and the risks of thromboembolism, bleeding complications, and mortality. Methods: The nationwide FinWAF study included 54 568 AF patients taking warfarin. Time in the therapeutic range (TTR) was calculated on a continuous basis using the Rosendaal method and international normalized ratio values over the previous 60 days. Adjusted Cox proportional hazard models were prepared for different TTR levels and major clinical end points. Results: The mean age of patients was 73.1 years (standard deviation 10.8), and 47% were female. The mean follow‐up time was 3.2 ± 1.6 years (median 3.4). In the TTR groups of ≤40%, 60–70%, 70–80%, and >80%, the annual risk of stroke was 9.3%, 4.7%, 4.6%, and 3.1%; bleeding events 7.5%, 4.5%, 4.3%, and 2.6%; and overall mortality 20.9%, 8.5%, 6.4%, and 3.1%, respectively. All differences among the TTR groups were highly significant ( p  < 0.001). Conclusions: The quality of warfarin treatment was strongly associated with the risk of stroke and the prognosis of AF patients. Patient outcomes continued to improve with increasing TTR values up to a TTR ≥80%; therefore, the target for the TTR should exceed 80% instead of the traditional range of at least 60–70%. Copyright © 2017 John Wiley & Sons, Ltd.